MAMPUKAH KEPEMILIKAN INSTITUSIONAL MEMODERASI DETERMINAN YANG MEMENGARUHI KEUANGAN BERKELANJUTAN PERUSAHAAN PERBANKAN? COULD THE INSTITUSIONAL OWNERHIP MODERATE THE DETERMINANTS THAT INFLUENCE SUSTAINABLE FINANCE OF BANKING COMPANIES ? - Alwi, Ade Rosadi; Lusmeida, Herlina (Universitas Riau, 2025)
This research aims to provide the emphirical evidence of the effect of bank’s health level, financial performance, and tax avoidance on sustainable finance with institutional ownership as a moderating variable. The data sources used in this study are banking companies that have assets of at least 5 trillion rupiah and are registered with the Otoritas Jasa Keuangan (OJK) for the 2019-2023 period, with a total of 231 samples. The research data was processed using a multiple linear regression model, with the results of the study proving that Bank’s Health Level have a negative effect on Sustainable Finance; Financial Performance has a positive effect on Sustainable Finance; Tax Avoidance and institutional ownership have no effect on Sustainable Finance; Institutional Ownership is unable to moderate the effect of Bank Health, financial performance and tax avoidance to sustainable finance. This study provides practical implications to encourage banking companies to increase their legitimacy through sustainable finance disclosures in their financial reports.This study also provides theoritical implication through stakeholder theory and institutional theory that bank as a financial institutional has to fulfil stakeholder needs, including monitoring mechanism by institutional ownership